Laparoscopic Artificial Insemination Technique in Small Ruminants—A Procedure Review - Sathe, Swanand R. (Frontiers in Veterinary Science, 2018)
Laparoscopic artificial insemination (LAI) is an intrauterine method of insemination, especially popular utilized in the small ruminant species to bypass their unique anatomically tortuous cervix. There are several advantages of LAI that include efficient use of processed semen leading to higher pregnancy rates. Success of LAI programs depends on proper implementation of estrus synchronization programs, patient selection and thorough knowledge of the reproductive physiology. In addition, proper equipment and surgical expertise help in reducing patient morbidity and mortality rates. LAI can be associated with several complications as a result of inadequate patient preparation, poor technique or equipment failure. Hence, a through planning is essential to carry out the procedure safely and with consistent success rates. Addition of LAI to a small ruminant/food animal practice can be quite profitable and professionally fulfilling, as long as an appropriate investment in equipment and adequate training of veterinarians and technical staff is implemented. Though the technique for performing LAI has been mentioned briefly through various research articles, this article serves as the first comprehensive review of the technique, equipment used, associated complications and useful practical tips that could serve as a guideline for clinicians interested in adding this service to their practice. The article also contains some novel research supported ideas to provide laparoscopic insufflation that have been recently developed.